THE MENTAL IMAGE OF THE IRAQI PUBLIC CONCERNING THE HOUSE OF REPRESENTATIVES: (Section I) - Gabar Al-Shemary, Ali Gabar Al-Shemary (ALBAHITH ALALAMI, 2022)
This research is a result of other studies made about the iraqi public and its relationship with different states institutions, until recently, such studies were almost non-existent. The main characteristic that distinguishes scientific research is that it involves a specific problem that needs to be studied and analysed from multiple aspects. What is meant by identifying the problem, is to limit the topic to what the researcher wants to deal with, rather than what the title suggests as topics which the researcher doesn’t want to deal with. The problem of this research is the absence of thoughtful and planned scientific programs to build a positive mental image of the institutions of the modern state in general and the House of Representatives in particular. Especially since the Iraqi citizens are not yet used to the existence of parliamentary life based on democratic foundations. Moreover, the relationship between the previous parliaments and the public has passed through a crisis of confidence as a result of the inability of these parliaments to perform their duties according to what the public wants, which may adversely affect the public's image of the current parliament. Also, the House of Representatives did not succeed during the first legislative term of its era in providing what the masses expected of it, this forced the Presidency of the Council to extend the legislative term for an additional month. If the research problem is concerned with answering questions raised by the researcher or with testing hypotheses dictated by the research requirements to achieve its objectives, this research tries to test a set of zero hypotheses based on the assumption that the results came from one community, and therefore there are no differences in the answers of the respondents.